CIRCULAR ECONOMIES RESOURCE EFFICIENCY, CHALLENGES AND OPPORTUNITIES FOR "GREEN" ECONOMY IN NORTH MACEDONIA - Janevski, Zoran; Krstic Tasheva, Violeta (Institute of Economics – Skopje, 2019)
Economic growth, increased consumption and irrational use of natural resources negatively affect the environment. Respecting resource constraints, the need to gradually change the existing unsustainable production and consumption model is emerging as one of the key challenges of sustainable development. The amount of waste is constantly increasing, and the characteristics of the waste are constantly changing in direction of its degradation, but also its negative impact on the environment, and thus the quality of life. The resource limitations, on the other hand, create an noncompetitive business environment, and this is a challenge to finding innovative technologies that will allow waste to be transformed into a resource. The aim of the research is waste as an opportunity for resource efficiency and “green” economy in North Macedonia. The survey shows that by increasing resource efficiency provides circular economic solutions that can generate economic growth and “green” jobs, and business entities increase their productivity and competitiveness.
Keywords: sustainable development; еnvironment; circular economy; resource effciency; waste